2012
DOI: 10.1002/em.21711
|View full text |Cite
|
Sign up to set email alerts
|

AFB1‐induced mutagenesis of the gpt gene in AS52 cells

Abstract: Aflatoxin B1 (AFB1) is a potent mutagen and an important risk factor for hepatocellular carcinoma (HCC) in humans. Transgenic mouse strains and cells in culture have been used to detect different types of mutations caused by AFB1 and investigate the molecular determinants of their location and frequency. The AFB1 mutational spectrum in the gpt gene was markedly different in AS52 cells compared to the liver in gpt delta B6C3F1 transgenic mice. The results demonstrate the importance of metabolism, chromosomal lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Using this model, we have established that PQ is mutagenic and cytotoxic, its properties stemming from its ability to generate ROS and induce genomic accumulation of oxidative DNA lesions such as 8OG. The system described is well poised to enable deeper analysis of PQ mutagenesis in terms of the specific types of point mutations induced, and mutational spectra, both in the AS52 cells, and in an animal model (e.g., B6C3F1 gpt delta mouse [34, 49]).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using this model, we have established that PQ is mutagenic and cytotoxic, its properties stemming from its ability to generate ROS and induce genomic accumulation of oxidative DNA lesions such as 8OG. The system described is well poised to enable deeper analysis of PQ mutagenesis in terms of the specific types of point mutations induced, and mutational spectra, both in the AS52 cells, and in an animal model (e.g., B6C3F1 gpt delta mouse [34, 49]).…”
Section: Discussionmentioning
confidence: 99%
“…To remove the spurious or pre-existing 6-thioguanine resistant (6-TG r ) mutants, cells were cultured in the presence of mycophenolic acid (MPA) (Sigma-Aldrich, USA) for 7 days. The MPA-containing medium was the complete medium (above) supplemented with 10 μg/ml MPA, 250 μg/ml xanthine (Sigma-Aldrich), 22 μg/ml adenine (Sigma-Aldrich), 11 μg/ml thymidine (Sigma-Aldrich), and 1.2 μg/ml aminopterin (Sigma-Aldrich) [33, 34]. Thereafter, cells were maintained in complete medium plus 11.5 μg/ml xanthine, 3 μg/ml adenine and 1.2 μg/ml thymidine for 3 additional days.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we found that the mutational spectrum and types of mutations induced by these two aldehydes were distinctly different (Figure 5C & 5D ). Most notably Acet induced mainly G to T transversion mutations (69%), which are the same as AFB1-induced G to T mutations in the p53 and gpt genes in human cells and yeast systems [ 40 42 ]. Cro, on the other hand, induced both G to T (37.5%) and G to C (40.6%) mutations at similar levels [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Underlines represent tandem mutations. Note: The percentages of G to T and A mutations induced by Acet are similar to that of induced by AFB1 [ 40 42 ].…”
Section: Resultsmentioning
confidence: 99%